2016
DOI: 10.3389/fmicb.2016.02098
|View full text |Cite
|
Sign up to set email alerts
|

A High-Level Fungal Diversity in the Intertidal Sediment of Chinese Seas Presents the Spatial Variation of Community Composition

Abstract: The intertidal region is one of the most dynamic environments in the biosphere, which potentially supports vast biodiversity. Fungi have been found to play important roles in marine ecosystems, e.g., as parasites or symbionts of plants and animals, and as decomposers of organic materials. The fungal diversity in intertidal region, however, remains poorly understood. In this study, sediment samples from various intertidal habitats of Chinese seas were collected and investigated for determination of fungal commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 63 publications
4
29
0
Order By: Relevance
“…Some members of these two phyla were found to be decomposers of pollen and leaves in marine habitats (Phuphumirat, Ferguson, & Gleason, ) or pathogens infecting marine algae and animals (Scholz, Küpper, Vyverman, & Karsten, ), suggesting a wide array of ecological roles potentially performed by these fungi in the ECS. Interestingly, among the five mycorrhizal genera in Glomeromycota detected in this study, four of them (i.e., Ambispora , Diversispora, Funneliformis and Glomus ) were previously found in intertidal sediments in Chinese seas (Li, Wang, Bian et al., ). Diversispora and Glomus were also retrieved from deep subseafloor sediments (Orsi, Biddle, & Edgcomb, ).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Some members of these two phyla were found to be decomposers of pollen and leaves in marine habitats (Phuphumirat, Ferguson, & Gleason, ) or pathogens infecting marine algae and animals (Scholz, Küpper, Vyverman, & Karsten, ), suggesting a wide array of ecological roles potentially performed by these fungi in the ECS. Interestingly, among the five mycorrhizal genera in Glomeromycota detected in this study, four of them (i.e., Ambispora , Diversispora, Funneliformis and Glomus ) were previously found in intertidal sediments in Chinese seas (Li, Wang, Bian et al., ). Diversispora and Glomus were also retrieved from deep subseafloor sediments (Orsi, Biddle, & Edgcomb, ).…”
Section: Discussionsupporting
confidence: 51%
“…Along the ECS coast, several rivers (e.g., the Yangtze and Qiantang rivers) discharge massive amounts of freshwater and sediment into the local ocean; for example, the Yangtze River discharges approximately 4.7–5.0 × 10 8 tons of sediment per year (Song, ). Some terrestrial or freshwater fungi in water and sediment were presumed to enrich the intertidal regions of the ECS and probably contribute to the large difference in fungal communities between the ECS and other sea regions of China (Li, Wang, Bian et al., ). In this study, we found that river run‐off markedly affects the water community structure, as highlighted by the dominance of the typical terrestrial fungus Byssochlamys sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, sand microbial assemblages have been proposed as a sensitive bio-indicator for evaluating the environmental health of coastal habitats [10,12]. In this regard, geographic distance has also been found to play a certain role in controlling the spatial distribution of sand microbial assemblages, suggesting that dispersal limitations may affect sand microbial communities as well [8,13]. In addition, disturbances like wave-or tidal-action may lead to the random dispersal of microbes between seawater and intertidal sands, or across the unsaturated zone of beach aquifers [2,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…PCR amplification was performed in a total volume of 50 µL reaction mixture containing 10 ng of template DNA, 10 × AccuPrime PCR buffer II (including dNTPs) (Invitrogen, United States), 0.2 U AccuPrime High Fidelity Taq Polymerase, and 0.4 mM of both forward and reverse primers. The primer pair used to amplify fungi was ITS3/ITS4 (Li et al, 2016). The paired Illumina adaptors were linked to the 5 end of the forward and reverse primers.…”
Section: Molecular Characterization Of Fungimentioning
confidence: 99%